CRITICISM ON WEBERIAN BUREAUCRATION: RADICAL SUBJECT PERSPECTIVE - Dodi Faedlulloh; Yulianto Yulianto; Intan Fitri Meutia; Devi Yulianti (Universitas Padjadjaran, 2023)
The Weberian narrative has become ingrained in the Indonesian bureaucracy has an impact on the fact that the bureaucratic reform agenda is not yet actual, so that public disappointment with the performance of the bureaucracy is still a general finding. The performance of the bureaucracy in Indonesia is still ineffective. To overhaul this order, Zizek’s thoughts on the subject deserve to be placed as a critical activity in exploring the role of the state civil apparatus (SCA). This study aims to read the authentic potential of bureaucrats as agents of change in bureaucratic reform in Indonesia by borrowing the analysis of the Zizekian radical subject. This research method uses a desk study by collecting data and information based on information analysis and secondary data. The results showed that basically SCA has an authentic capacity as a radical subject, in this case the subject of reform which is able to overthrow the Weberian bureaucratic structure that has become the shackles of the Symbolic One. This can be done by organizing the subject of reform collectively which is continually breaking the Weberian bureaucracy. The important implication of this study is as an anchor for SCAs who believe in the importance of change in the bureaucratic environment and that their role is very important as agents of reform subjects who dare to risk themselves taking action towards better bureaucratic reform.